Who Is Willing to Engage in Social Gatherings During the Coronavirus Disease 2019 Lockdown? A Curvilinear Relationship Between Age and Heuristic Processing - Wang, Kexin; Li, Siyue (Frontiers in Psychology, 2020)
Background: The Chinese government implemented a lockdown to contain the COVID-19 pandemic during the Chinese Lunar New Year when people have the tradition to visit families and friends. Previous research suggested that heuristic processing increased risky behavioral willingness (e.g., desire to have social gatherings despite the pandemic) and that people’s tendency to use heuristic processing varied across different adulthood stages. This study thus investigated the relationships among age, heuristic processing of COVID-19 related information, and the willingness to have social gatherings during the lockdown. Methods: A sample of 1,651 participants was recruited from an online crowdsourcing platform between Jan. 31 and Feb. 4 in 2020, with a mean age of 30.69, 47.9% being women. Participants completed an online questionnaire about heuristic processing of the COVID-19 related information, willingness to engaging in social gatherings during the lockdown, age, and other demographic information. Results: Age was found to have a U-shaped curvilinear relationship with heuristic processing, and heuristic processing was positively correlated with the willingness to have social gatherings. Further analyses showed that heuristic processing curvilinearly mediated the relationship between age and the willingness to have social gatherings. Conclusion: Compared with young adults, emerging and older adults are more likely to engage in heuristic processing, which in turn, increases the willingness to have social gatherings. Heuristic processing serves as an underlying mechanism to explain the relationship between age and risky behavioral willingness.